PERISTIWA TUTUR BERDASARKAN ASPEK “SPEAKING” DALAM TAYANGAN “KATAKAN PUTUS” - Fikri Najiyah; Rezza Ayda Mutiara; Riana Dwi Lestari (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Mass media has progressed more rapidly from time to time, one of which is television media that has enormous potential than other electronic media. This observation intends to understand the speech events in the Say Disconnect show. The object of this observation is a conversation from participants in the Disconnect Say. The research method used is qualitative. As a result, the research proves that the whole dialogue in the Say Broken scene piece fulfills the eight SPEAKING requirements to become a speech event. In this episode, there are 34 speeches. The main topic is about the problem of love of a client named Indri. On the Settings, there are two background places named in the car and in the dance studio. Participants, there are five participants namely Komo, Concita, Indri, Bagus, and Dance Coaches. Ends or designed and intended from this show is solving a client's love problem. In the action sequences, the form of speech in this show is in the form of dialogue conversation. The various languages used in all are unofficial languages. Found a lot of keys that are used so that you can say expressive in every conversation. Instrumentalities that are used in the whole conversation are oral with a variety of informal languages. In Norm, there are interacting norms in the form of politeness when speaking. In Genres or forms of delivery in the form of dialogue.